Analisis Pengaruh Konsumsi Listrik dan Konsumsi Bahan Bakar Fosil Terhadap Eksternalitas Negatif Emisi Gas Rumah Kaca di Indonesia - Peni Rachmawati Hanifah; I. B. Putu Purbadharmaja (Jurnal Visi Manajemen, 2025)
The current warming trend is a negative externality of human activities since the mid-1800s and is proceeding at a pace unprecedented over the past millennia, such as increased energy consumption leading to an increase in the concentration ofCO2 gas and other gases in the atmosphere. CO2 gas has the largest contribution to global warming at about 56%. Increased energy consumption that causes an increase inCO2 gas because the use of energy consumption in Indonesia is still dominated by fossil energy consumption produced from fossil fuels and often uses technology that is not environmentally friendly so that it can trigger an increase in Greenhouse Gas (GHG) emissions which is the largest contributor to global warming. In response to this warming trend, Indonesia has ratified the Kyoto Protocol in 1997 into Law Number 17 of 2004 and the Paris Agreement into Law Number 16 of 2016 in an effort to reduce the temperature rise limit to 1.5°C above the earth's temperature in pre-industrial times. The objectives of this study are (1) To analyze the effect of electricity consumption and fossil fuel consumption simultaneously on the negative externalities of GHG emissions in Indonesia. (2) To analyze the effect of electricity consumption and fossil fuel consumption partially on the negative externalities of GHG emissions in Indonesia. The data used is secondary data, with multiple linear analysis techniques. The results showed that (1) Electricity consumption and fossil fuel consumption simultaneously affect the negative externalities of GHG emissions in Indonesia. (2) Electricity consumption partially has a positive and significant effect on the negative externalities of GHG emissions in Indonesia. (3) Fossil fuel consumption partially has a positive and insignificant effect on the negative externalities of GHG emissions in Indonesia. Keywords: Greenhouse Gas, Negative Externalities, Energy Consumption, Electricity Consumption, Fossil Fuel Consumption